Personal and social responsibility among athletes: the role of self-determination, achievement goals and engagement - Martins, P.; Rosado, A.; Ferreira, V.; Biscaia, R. (Journal of Human Kinetics, 2017)
The purpose of this study was to assess the relationship between motivation, engagement and personal and social responsibility among athletes. Based on the literature, a survey was conducted including measures of motivation, considering task orientation and ego orientation, intrinsic and extrinsic motivation, and amotivation. We also measured the components of engagement (dedication, confidence, vigor and enthusiasm) and the components of personal and social responsibility. A total of 517 athletes from different types of sports participated in the study. The results gathered through a structural equation model revealed that task orientation had the strongest relationship with personal responsibility and social responsibility, followed by engagement. Self-determination levels were not associated with personal and social responsibility. These results suggest that monitoring of task orientation and engagement levels should be performed by coaches as a strategy to develop personal and social responsibility among their athletes. Moreover, findings from this study provide scholars with a tool to aid them in managing athletes` levels of personal and social responsibility.